2015
DOI: 10.3390/f6041179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Smartphone App for Forest Sample Plot Measurements

Abstract: Abstract:We evaluated a smartphone app (TRESTIMA TM ) for forest sample plot measurements. The app interprets imagery collected from the sample plots using the camera in the smartphone and then estimates forest inventory attributes, including species-specific basal areas (G) as well as the diameter (DgM) and height (HgM) of basal area median trees. The estimates from the smartphone app were compared to forest inventory attributes derived from tree-wise measurements using calipers and a Vertex height measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 19 publications
3
27
1
1
Order By: Relevance
“…Yao et al [40] reported R 2 = 0.66 (lower than the Relasphone results in Finland) for plot-level basal area estimation with TLS, but a slightly better agreement for biomass (R 2 = 0.85), similar to the best results for pine and total stem volume in Mexico. The accuracies of the commercial forest inventory app Trestima was reported on 25 plots from another site in southern Finland [46]. The relative RMSE for Relasphone-based total basal area in Finland (RMSE(%) = 29.66%; Table 4) was comparable to that of Trestima (19.7%-29.3%) and slightly better in Mexico (RMSE(%) = 17.21%-18%).…”
Section: Relasphone Measurements Versus Other Forest Mensuration Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…Yao et al [40] reported R 2 = 0.66 (lower than the Relasphone results in Finland) for plot-level basal area estimation with TLS, but a slightly better agreement for biomass (R 2 = 0.85), similar to the best results for pine and total stem volume in Mexico. The accuracies of the commercial forest inventory app Trestima was reported on 25 plots from another site in southern Finland [46]. The relative RMSE for Relasphone-based total basal area in Finland (RMSE(%) = 29.66%; Table 4) was comparable to that of Trestima (19.7%-29.3%) and slightly better in Mexico (RMSE(%) = 17.21%-18%).…”
Section: Relasphone Measurements Versus Other Forest Mensuration Methodsmentioning
confidence: 68%
“…Automatic image processing was investigated by Molinier et al in 2011 [45], and the interactive Relasphone application (http://www.relasphone.com) was released for free. Since then, similar smartphone apps have been proposed, such as MOTI for professional foresters and Trestima, a commercial application developed in 2012 that sends images to a server for automatic or semi-automatic processing [46]. To our knowledge, Relasphone measurements are the only ones that were extensively tested versus reference forest inventory plot data in two different biomes-boreal zone in Finland [47] and temperate zone in Durango, Mexico [48]-then combined with satellite images to produce maps of growing stock volume (GSV) or aboveground biomass (AGB).…”
Section: Introductionmentioning
confidence: 99%
“…Calipers, a device used to measure the distance between two opposite sides, can easily measure the diameter or cross-section of a tree trunk [10]. With advancements in equipment, modern methods of collecting forest inventory data include laser rangefinders [11], terrestrial light detection and ranging (LiDAR; [12,13]), and even smartphone applications [14], which improve efficiency and data quality. Although different methods can be used to collect forest data depending on various technologies and their suitability, the methods must always be used on the ground.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, [18] used a novel approach for acquisition of forest horizontal structure (stem distribution) with panoramic photography or a similar technique which may be applied through smartphone [19]; however, a recent technique using multi-view stereopsis (MVS) combined with computer vision and photogrammetry, for example [20], alongside algorithms such as Scale-invariant feature transform (SIFT) [21] or Speeded Up Robust Features (SURF) [22], allows the use of common optical cameras for the reconstruction of 3D objects to improve the architectural representation of tree stems and crown structures as, for example, demonstrated in [23,24]. The reconstruction is based on automatic detection of the same points, i.e., stem or crown features, in subsequent paired images.…”
Section: Introductionmentioning
confidence: 99%